2019
DOI: 10.1021/acs.organomet.8b00898
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Tunable Cyclization of Formamidinate Ligands in Carbonyl Complexes of Mn(I): An Experimental and Theoretical Study

Abstract: A subtle change in the substituents at the nitrogen atoms in the N,N′-diarylformamidine complexes of formula fac-[Mn­(RNC­(H)­NHR)­(bipy)­(CO)3]+ (1a, R = phenyl; 1b, R = 4-dimethylaminophenyl) produces, upon deprotonation, either the monodentate formamidinate complex fac-[Mn­(PhNC­(H)­NPh)­(bipy)­(CO)3] (2a) or metallacylic complex 3b, which features a carbamoyl residue arising from nucleophilic attack to a vicinal carbonyl ligand. Complexes type 3 are also formed when using N-aryl-N′-alkyl-formamidines as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Not surprisingly, between 75% and 85% of the contribution at both C5-Br1 and C5-Br2 bcps comes from the two bonded atoms, with only very small contributions from other atoms, like S1 ($5%) and the other bromine atom (Br2 and Br1, respectively, $5%), which are the other major contributions (other minor contributions are not included in Table 5). This is a well known result for covalent bonds, which has been found previously in many instances (Gatti & Lasi, 2007;Ruiz et al, 2019). Rather interestingly, for the Br2Á Á ÁBr3 interaction as well, more than 85% of the contribution comes from both bonded atoms, as in typical covalent bonds.…”
Section: Resultssupporting
confidence: 78%
“…Not surprisingly, between 75% and 85% of the contribution at both C5-Br1 and C5-Br2 bcps comes from the two bonded atoms, with only very small contributions from other atoms, like S1 ($5%) and the other bromine atom (Br2 and Br1, respectively, $5%), which are the other major contributions (other minor contributions are not included in Table 5). This is a well known result for covalent bonds, which has been found previously in many instances (Gatti & Lasi, 2007;Ruiz et al, 2019). Rather interestingly, for the Br2Á Á ÁBr3 interaction as well, more than 85% of the contribution comes from both bonded atoms, as in typical covalent bonds.…”
Section: Resultssupporting
confidence: 78%
“…Landis and co-workers questioned the method of bonding analysis and suggested that the alkaline earth octacarbonyls are mainly bonded by ionic interactions between M 2+ and [(CO) 8 ] 2– . , Koch and co-workers challenged the interpretation of the red-shift of the CO stretching frequencies of Ca­(CO) 8 in terms of π-backbonding from the d AOs of calcium, because calculations of the complex without d AOs of Ca reproduce the stretching frequencies quite well. Van der Maelen also disputed the relevance of the d AOs of Ca, Sr, Ba for the M → (CO) 8 π-backdonation and suggests that the red-shift of the CO stretching frequencies is instead due to interligand interactions between the CO ligands . The arguments of the author are based on real-space partitioning methods, which had previously been used for analyzing the nature of metal–CO interactions in transition metal complexes. An earlier study by Pendás and co-workers using the IQA (Interacting Quantum Atoms) method ,, showed that the results of the IQA calculations basically support the DCD model concerning the relevance of π-backdonation for the red-shift of the C–O stretching frequencies in carbonyl complexes, but the calculated values of the delocalization indices (DI) suggest a possible multicenter bonding among the ligands in some carbonyl complexes such as [V­(CO) 6 ] − , Cr­(CO) 6 , and [Fe­(CO) 6 ] 2+ . Since the DI values of the alkaline earth octacarbonyls deviate even stronger from those of classical carbonyl complexes, Van der Maelen concluded that the DCD model is not valid for the M–CO interactions in M­(CO) 8 (M = Ca, Sr, Ba). …”
Section: Introductionmentioning
confidence: 99%
“…Then, we can assume that no direct M-M bonding exists 22 . Other ligands in bridging sits, such as carbonyl 23,24 , Borylenes 25 , and Alkynes 26 , have also shown this loss of M-M bond paths. Also, RCPs located slightly closer to the geometrical centers of each M-H-M-H and Cp ligand were observed for cluster 1.…”
Section: Electron Density Topological Analysismentioning
confidence: 95%